PENERAPAN MODEL PEMBELAJARAN INQUIRY LEARNING PADA KEGIATAN BIMBINGAN BELAJAR DI SMA NEGERI 1 TANJUNG MORAWA - Manurung, Rolan; Sitorus, Enjelita Dewi Br.; Rajagukguk, Risnauli (Gapenas Publisher, 2025)
This Community Service (PkM) activity aims to describe the application of the Inquiry Learning model in tutoring activities at SMA Negeri 1 Tanjung Morawa and evaluate its effectiveness in increasing student engagement and learning outcomes. The Inquiry Learning model, which emphasizes the process of actively seeking and discovering knowledge by students, is applied in tutoring sessions as an effort to create a more interactive and participatory learning atmosphere. The method of implementing this activity is carried out in the form of community service. The activity was carried out from 06-26 February 2025 at SMA Negeri 1 Tanjung Morawa. The implementation of this activity was carried out by HKBP Nommensen University Students Medan. The number of students who participated in the PkM activity was 3 people and the students who were prioritized were class X students at SMA Negeri 1 Tanjung Morawa. The results of the study showed that the application of this model was able to increase student learning motivation, strengthen conceptual understanding, and encourage students to think critically and independently. In addition, the supervising teacher acknowledged that this approach had a positive impact on the dynamics of the study group and built more open communication between students and teachers. These findings indicate that the Inquiry Learning model can be a strategic alternative in improving the quality of tutoring, especially at the secondary education level. Thus, the integration of this learning model is recommended to continue to be developed and adjusted to the needs of students and the learning context in schools.